Predicting freshmen’s academic adjustment and subsequent achievement: differences between academic and professional higher education contexts - Willems, Jonas; van Daal, Tine; Van Petegem, Peter; Coertjens, Liesje; Donche, Vincent (Frontline Learning Research, 2021)
This study tests an integrative model, which delineates how students’ academic motivation, academic self-efficacy and learning strategies (processing strategies and regulation strategies) at the end of secondary education impact academic adjustment in the first semester of the first year of higher education (FYHE) and subsequent academic achievement at the end of the FYHE, in two types of HE programmes. More precisely, the present study explores the extent to which the explanatory values of aforementioned determinants of academic adjustment and academic achievement differ across academic (providing more theoretical and scientific education) and professional (offering more vocational education that prepares students for a particular occupation, such as nursing) programmes. Hereto, multiple-group SEM analyses were carried out on a longitudinal dataset containing 1987 respondents (Academic programmes: N=1080, 54.4%; Professional programmes: N=907, 45.6%), using Mplus 8.3. Results indicate differences in the predictive power of determinants under scrutiny between professional and academic contexts. Firstly, learning strategies and motivational variables at the end of secondary education have more predictive power in the prediction of FYHE academic adjustment in the academic programmes than in professional programmes. Secondly, our results indicate that academic adjustment in the first semester of the FYHE influences academic achievement to a bigger extent in professional programmes than in academic programmes. Moreover, these differences across HE contexts were found after controlling for prior education. Implications of the findings are discussed.